The Impact of Transformational Leadership and Work Environment on Teachers’ Performance in Crisis-Affected Educational Settings - Soha El Achi; Nada Jabbour Al Maalouf; Hwayda Barakat; Jeanne Laure Mawad (Administrative Sciences, 2025)
This study investigates the impact of transformational leadership and the work environment on teacher performance, with a particular focus on how the work environment moderates this relationship within crisis-affected educational settings. A quantitative, survey-based approach was adopted, utilizing a random sample of 509 teachers from various schools across Lebanon. Data analysis was conducted using Smart PLS 4 to assess direct and moderating relationships. The results reveal that while the work environment has a strong and significant positive effect on teacher performance, transformational leadership does not exhibit a statistically significant direct impact. This contrasts with prior studies conducted in stable educational settings, where transformational leadership has consistently been linked to improved teacher performance. The findings suggest that prolonged socio-economic and political crises shift teachers’ reliance more toward a supportive work environment, as basic stability and resource availability become more critical determinants of performance. In such conditions, leadership effectiveness appears contingent on the presence of a positive work environment. This study contributes to the literature by highlighting the fundamental role of the work environment in shaping leadership effectiveness and teacher performance in crisis contexts. It offers empirical insights to inform leadership practices and policy interventions in fragile educational systems.